Handbook of research on project management strategies and tools for organizational success - Moreno Monsalve, Nelson Antonio, 1978-; Diez-Silva, Mauricio, 1975-; Diaz Piraquive, Flor Nancy, 1964-; Pérez Uribe, Rafael Ignacio (Advances in logistics, operations, and management science (ALOMS) book series., 2020)
"This book analyzes and disseminates new trends in project management strategies and tools for organizational success"--